Faktor yang Mempengaruhi Kejadian Pneumonia pada Balita di Wilayah Jawa Timur Menggunakan Analisis Regresi Linier Berganda - Muhammad Riza Mahasin; Mahmudah (Media Gizi Kesmas, 2023)
Background: Pneumonia is one of the leading causes of death in children worldwide. Pneumonia in East Java. is in second place with a total of 93,238 cases, as of 2014. The achievement of finding pneumonia cases requires attention from various parties, both the government and the health department. Some of the risk factors that cause it are maternal characteristics, factors in children under five and environmental factors. Objective: This article aims to analyze the factors that influence the incidence of pneumonia in children under five in East Java using multiple linear regression analysis. Methods: The population in this study were families with under-fives with pneumonia spread over 38 cities / districts in the East Java region which were successfully recorded by the Central Statistics Agency per year 2018. The type of data used was secondary data which was analyzed using multiple linear regression methods. Result: Mojokerto City is the city that has the highest percentage of children under five exposed to pneumonia in East Java. The results of the study found that there was no effect of education level, home condition and economic level on under-five pneumonia in East Java. Conclusion: Factors that affect the level of pneumonia in East Java are the level of family education and healthy home conditions which have a significant effect on pneumonia under five in East Java, either simultaneously or partially.